Suscetibilidade entre raças de ovinos experimentalmente infectados com o sorogrupo de Leptospira Pomona - Costa, D. F.; Silva, M. L. C. R.; Martins, G.; Dantas, A. F. M.; Melo, M. A.; Azevedo, S. S.; Lilenbaum, W.; Alves, C. J. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a disease that negatively affects the productive and reproductive indices of ruminants. Sheep are considered highly resistant to infection, although susceptibility may vary among breeds.